Architectural phenomenology: Past, present, future of an interdisciplinarity - Qing Liu (Frontiers of Architectural Research, 2025)
This article investigates the interdisciplinary nature of what is frequently referred to as architectural phenomenology. By highlighting the intricacy of architecture's disciplinarity, it exposes the paradoxical attitude of architectural phenomenology towards crossing disciplinary borders, and sets out to contextualize the paradoxical attitude about interdisciplinary research in history. Following three thematic threads representative of the tradition centered on Ernesto Nathan Rogers, Christian Norberg-Schulz, and the Essex school, it showcases the diverse modalities of how architecture and phenomenology were combined in the past, and identifies a significant gap in their limited interpretations of the relation between these two fields, often characterized by a one-sided illumination. Drawing attention to the insufficiently theorized reciprocity between architecture and philosophy, it reveals in architectural phenomenology an interdisciplinary interplay implicitly involving all other disciplines, which offers unlimited possibilities of research to be further explored. Taking a closer look at the interdisciplinary nature of architecture and phenomenology, it speculates on the future directions of architectural phenomenology acting as an interdisciplinary arena, pointing to phenomenology's recent interest in enactivist cognitive science and architecture's critical engagement with socio-political issues that converge in an investigation of the built environment.